Culture Conditions for the Production of Cellulase by Trichoderma reesei Rut - KIRAN, OZLEM (Asian Journal of Chemistry, 2010)
Effects of pH values and peptone concentrations on the production of cellulases by Trichoderma reesei RUT were investigated in this study. Trichoderma strains, particularly Trichoderma reesei RUT is the excellent sources of cellulase suitable for practical applications. Enzyme production was observed at pH 3.5, 4.0 and 4.5 in 0.05 and 0.1 % peptone containing mediums for 4 d. The activity of cellulase was measured by using carboxymethylcellulose (CMC) as the substrate. According to results the maximum specific activity was obtained in 0.5 % peptone containing medium in 72 h at pH 4.0, 0.05 % peptone containing medium at 96 h at pH 4.5.